Electron doping and magnetic moment formation in Nand C-doped MgO - Sanvito, Stefano; Droghetti, Andrea (My University, 2009)
The formation of the magnetic moment in C- and N-doped MgO is the result of a delicate interplay between Hund?s coupling, hybridization, and Jahn?Teller distortion. The balance depends on a number of environmental variables including electron doping. We investigate such a dependence by self-interaction corrected density functional theory and we find that the moment formation is robust with respect to electron doping. In contrast, the local symmetry around the dopant is more fragile and different geometries can be stabilized. Crucially the magnetic moment is always extremely localized, making any carrier mediated picture of magnetism in d0magnets unlikely.
PUBLISHED
Keywords: Physics; Nanoscience & Materials